About Education in Architecture: Visual Spaces of Change (EAAE Annual Conference Proceedings, 2023)
This abstract is based on the didactic experience and refinement of three curricular units (CUs) in FAUP, which are Photography and Design Communication, articulated with Photography of Architecture, City and Territory. In addition to this, the consolidation of a research work on the uses of diverse visual strategies and representation methods for communicating architecture, city and territory, with a special focus on photography as a transversal media within these areas of study.